Heterogeneous High-Performance System Algorithm Based on Computer Big Data Technology - Pan, Dongyang (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: In this paper, a scheduling algorithm for heterogeneous systems based on prioritization (PQDSA) is proposed. This algorithm is a sort method based on directed acyclic graph (DAG). The key nodes in the network are grouped according to the communication and computing costs in the network. This increases the parallelism between task schedules and reduces the completion time of work sets. Then, a method of assigning multiple tasks to multiple processors using interpolation is proposed. The PQDSA method can effectively reduce the time of scheduling multiple tasks and improve the scheduling effect. PQDSA is compared with EDL-θ and EDF scheduling methods. The results show that this method has better scheduling efficiency.